Dental caries and family expenditures as determinants of oral health-related quality of life in children, in Gamping, Sleman, and Yogyakarta - Rizka Wahyuni; Lisdrianto Hanindriyo; Sri Widiati (Majalah Kedokteran Gigi Indonesia, 2021)
Inadequate oral health conditions would prevent children from participating in normal activities, which in turn would lead to changes in the children’s development and well-being. The aim of the study was to know whether dental caries and family expenditure are associated with quality of life related to dental and oral health among children aged 10–12 years. This study was conducted using observational quantitative with cross-sectional design. The research respondents were 126 students (n= 126) aged 10–12 years who were attending elementary school in Gamping Subdistrict, Sleman Regency, Yogyakarta. The respondents were selected based on proportional random sampling by applying inclusion and exclusion criteria. Quality of life related to dental and oral health assessment was done using CPQ11-12 ISF-16 version regarding their dental caries status (DMF-T) and family expenditure. The results of this study, based on Pearson’s correlation analysis showed that dental caries status and family expenditure were significantly correlated with quality of life related to dental and oral health (p = 0.013 and p = 0.001). The findings of multiple regression analysis suggested significant effects of family expenditures and caries status on quality of life related to dental and oral health (p = 0.001 and p = 0.037) and R2 = 0.161. Lower dental caries was associated with better quality of life related to dental and oral health. Higher family expenditure was associated with better quality of life related to dental and oral health. Dental caries status and family expenditure contributed to 16.1% of quality of life related to dental and oral health.